Naphthenic acid extraction and speciation from Doba crude oil using carbonate-based ionic liquids. (15th April 2015) - Anderson, K.; Atkins, M.P.; Goodrich, P.; Hardacre, C.; Hussain, A.S.; Pilus, R.; Rooney, D.W.
Highlights: Carbonate-based ionic liquids can be used to remove naphthenic acids from crude oil. The reaction mechanism involves the formation of an ionic liquid-naphthenic acid complex. The complex can be reacted with carbonic acid to reform the ionic liquid. Recycling of the ionic liquid has been demonstrated. Abstract: A number of tetraalkylammonium methylcarbonate and hydrogencarbonate based ionic liquids are shown to be capable of reacting with the naphthenic acids contained in Doba crude oil via a neutralisation reaction. Spectral studies show that the ionic liquids neutralisation mechanism involves the formation of an ionic liquid-naphthenate complex, liberating methanol and carbon dioxide. Extraction of the neutralised complex into a separate methanol phase and subsequent regeneration using aqueous carbonic acid results in ∼70% of the ionic liquid being recovered for recycle. Isolation of the naphthenic acids shows that these make up to 0.85 wt% of the crude oil. Speciation of the naphthenic acids shows a mixture of monocyclic, through to tetracyclic structures with carbon numbers in the range C12 –C40 .